Deep Ocean Ventilation: A Comparison Between a General Circulation Model and Data‐Constrained Inverse Models - Bruno Millet; Casimir de Lavergne; William R. Gray; Christian Éthé; Gurvan Madec; Mark Holzer; Tim DeVries; Geoffrey Gebbie; Didier M. Roche (Journal of Advances in Modeling Earth Systems)
Abstract Ocean ventilation, or the transfer of tracers from the surface boundary layer into the ocean interior, is a critical process in biogeochemical cycles and the climate system. Here, we assess steady‐state ventilation patterns and timescales in three models of ocean transport: a 1° global configuration of the Nucleus for European Modeling of the Ocean (NEMO), a recent 2° solution of the Ocean Circulation Inverse Model (OCIM), and a 2° solution of the Total Matrix Intercomparison (TMI). We release artificial dyes in six surface regions of each model and compare equilibrium dye distributions as well as ideal age distributions. We find good qualitative agreement in large‐scale dye distributions across the three models. However, the distributions indicate that TMI and OCIM are more diffusive than NEMO. A shallow bias of North Atlantic ventilation in NEMO contributes to a stronger presence of the North Atlantic dye in the mid‐depth Southern Ocean and Pacific. This isopycnal communication between the North Atlantic surface and the mid‐depth Pacific is very slow, however, and NEMO simulates a maximum age in the North Pacific (NP) about 900 years higher than the data‐constrained models. Overly slow NP ventilation persists across NEMO sensitivity experiments encompassing our current best knowledge of diapycnal and isopycnal mixing, pointing to biases in subarctic Pacific dynamics. This study provides a synoptic picture of deep ocean ventilation and a framework for assessing its representation in general circulation models.